Airline efficiency measures under CNG2020 strategy: An application of a Dynamic By-production model. (December 2017) - Cui, Qiang; Li, Ye
Highlights: The efficiencies of 29 large global airlines under CNG2020 strategy are evaluated. A Dynamic By-production model is proposed. The efficiency of pollution causing inputs is more important in deciding the overall efficiency change. These airlines cannot meet the requirement of CNG2020 strategy in current situation. Abstract: We evaluate airline dynamic efficiency under the background of "Carbon Neutral Growth from 2020" strategy (CNG2020 strategy). The data of 29 large global airlines from 2021 to 2023 is predicted by BP neural network based on the historical data of 2008–2015. A new model, Dynamic By-production model, is proposed to measure the dynamic efficiencies of these 29 airlines during 2021–2023. The main findings are: (1) Aeroflot, Air Berlin, Ryanair, Finnair, Virgin Atlantic and Eva Air are the benchmarking airlines. (2) The efficiency of pollution causing inputs is more important in deciding the overall efficiency change. (3) These airlines cannot meet the requirement of CNG2020 strategy in current situation.